If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(7x) + -6(-7 + -1x) = 36 Remove parenthesis around (7x) -1 * 7x + -6(-7 + -1x) = 36 Multiply -1 * 7 -7x + -6(-7 + -1x) = 36 -7x + (-7 * -6 + -1x * -6) = 36 -7x + (42 + 6x) = 36 Reorder the terms: 42 + -7x + 6x = 36 Combine like terms: -7x + 6x = -1x 42 + -1x = 36 Solving 42 + -1x = 36 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-42' to each side of the equation. 42 + -42 + -1x = 36 + -42 Combine like terms: 42 + -42 = 0 0 + -1x = 36 + -42 -1x = 36 + -42 Combine like terms: 36 + -42 = -6 -1x = -6 Divide each side by '-1'. x = 6 Simplifying x = 6
| 2x+40=8 | | 6(4x-8)=3(12x+6) | | |40-7x|=15 | | 6-4(3a-2)= | | 0.50x+0.35(50)=44.5 | | 7x-(3x+9) | | 7d-3c-d= | | 3a^2+4a=21 | | 3x-6=--6 | | 7x+4+8x+6 | | 23-9p=18-4p | | 10+8x=16+6x | | 1/3x+1/4z=7 | | 3(x-1)-90=0 | | 136-7x=20x+22 | | 6-4(3a-2)=2(a+5) | | 10(v+2)-4v=3(2v+4)-21 | | 6x+2=-7+3x+21 | | leastcommondenominatorfor7,9,6 | | 7-8x=92-43 | | 3(1+c)=2(c-1) | | -9/3-y | | x^4-7x^3+11x^2-7x+10 | | 6(x-3)+2=9 | | 6(c-3)+2=9 | | 9x-7x+2x-6x= | | x-10-3/3-y | | 0,24*(-25/6) | | 3(1+c)-9=0 | | 2x-3+9=6 | | 2(3x+4)90 | | 7z=18-32 |